Improving esthetics after Silver Diamine Fluoride (SDF) treatment – Need of the Time! - Goswami, Mridula; Singh, Archana (International Journal of Dental Materials, 2024)
Background: Silver diamine fluoride (SDF) is a non-invasive, low-cost, antibacterial solution that has been introduced to potentially arrest active carious lesions. However, poor aesthetics is the main disadvantage, as it causes black staining on treated teeth.Aim: This study aimed to compare the ability of two different materials, Glass Ionomer Cement (GIC) and Giomer, to mask the discolouration caused by SDF on extracted deciduous molars. Materials and methods: Twenty carious primary molars indicated for extraction were selected and allocated to two groups. The samples in Groups 1 and 2 were restored with GIC and giomer, respectively, after SDF application. Colour measurement was done using a Spectrophotometer and compared between the two groups. The data were subjected to statistical analysis. The level of significance was assessed at p-value less than 0.05.Results: A statistically significant difference (p=0.001) was observed in the colour masking efficacy of Group 1 and Group 2, and the intergroup comparison also revealed statistically significant findings.Conclusion: This study found that both materials had significant masking abilities and reduced the discolouration caused by SDF application.